Auguste Comte (2006)
Auguste Comte is widely acknowledged as the founder of the science of sociology and the 'Religion of Humanity'. In this fascinating study, the first major reassessment of Comte’s sociology for many years, Mike Gane draws on recent scholarship and presents a new reading of this remarkable figure. Comte’s contributions to the history and philosophy of science have decisively influenced positive methodologies. He coined the term ‘sociology’ and gave it its first content, and he is renowned for having introduced the sociology of gender and emotion into sociology. What is less well known however, is that Comte contributed to ethics, and indeed coined the word ‘altruism’. In this important work Gane examines Comte's sociological vision and shows that, because he thought sociology could and should be reflexive, encyclopaedic and utopian, he considered topics such as fetishism, polytheism, fate, love, and the relations between sociology, science, theology and culture. This fascinating account of the birth of sociology is an unprecedented introductory text on Comte. Gane’s work is an essential read for all sociologists and students of the discipline.